Interdependencies Between the Capital Market and the Monetary Policy Decisions - Claudia Guni (Studies and Scientific Researches: Economics Edition, 2010)
The declared scope of this work is to highlight the main correlations between the monetary and the capital market, including identifying the adequate objective of monetary policy which might positively influence over the offer on the capital market. The main target of the monetary market consists in the stability of the prices. The link between monetary policy and stock market is extremely important. The stock prices are sensible to economical conditions. Moreover, these prices rapidly change, thus there is a chance for a deviation from the fundamental value, with side-effects for economy.